Analysis of characteristics of intracranial cavernous angioma and bleeding factors in middle-aged and elderly patients - Xiu, Chao; Ni, Donghe; Zhao, Jincui; Yu, Yang (Frontiers in Neurology, 2023)
Objective: Intracranial cavernous angioma is a cerebrovascular malformation. It causes local neurological dysfunction, epilepsy, intracranial haemorrhage and other symptoms, seriously affecting the safety of patients. The purpose of this study was to analyse middle-aged and elderly patients with ICA in our hospital, summarise the characteristics of the disease and analyse the related factors of ICH. Methods: We conducted a retrospective analysis of 120 middle-aged and elderly patients who were diagnosed with ICA by magnetic resonance imaging in our hospital from March 2018 to September 2021. All cases were assigned to a bleeding group(i.e. the experimental group) and a non-bleeding group(i.e. the control group). The characteristics of the disease, including gender, age, number of lesions, form and symptoms of onset, distribution of lesions, blood supply vessels in the lesion area, size of the lesion and presence of bleeding, were summarised and analysed. The relationship between these factors and ICH was investigated, and the data were analysed using SPSS 25.0 software. Results: There were 56 cases in the experimental group and 64 cases in the control group. A univariate analysis showed that gender, age, body mass index, blood lipids, number of lesions, course of the disease, onset of symptoms and disease characteristics were not associated with ICH in middle-aged and elderly patients with ICA(P>0.05). The maximum diameter, volume, location and blood supply area of lesions were related to ICA complicated with ICH(P<0.05). A multivariate unconditional logistic regression analysis revealed that the maximum diameter, volume, location and blood supply area of lesions were independent risk factors for ICH in middle-aged and elderly patients with ICA. The odds ratio of the maximum diameter of the lesion was 4.410, the OR of the lesion volume was 7.316, the OR of the lesion site was 7.470, and the OR of the blood supply area was 1.6588. Conclusion: Intracranial cavernous angioma lesions in middle-aged and elderly patients occur mainly in the supratentorial area, with a small part located in the infratentorial area. The main form of the disease is chronic recurrence. The occurrence of bleeding is related to the size, location and blood supply of the lesion.